Carbon nanotube-wrapped Fe2O3 anode with improved performance for lithium-ion batteries - Gao, Guoliang; Jin, Yan; Zeng, Qun; Wang, Deyu; Shen, Cai (Beilstein Journal of Nanotechnology, 2017)
Metall oxides have been proven to be potential candidates for the anode material of lithium-ion batteries (LIBs) because they offer high theoretical capacities, and are environmentally friendly and widely available. However, the low electronic conductivity and severe irreversible lithium storage have hindered a practical application. Herein, we employed ethanolamine as precursor to prepare Fe2O3/COOH-MWCNT composites through a simple hydrothermal synthesis. When these composites were used as electrode material in lithium-ion batteries, a reversible capacity of 711.2 mAh·g−1 at a current density of 500 mA·g−1 after 400 cycles was obtained. The result indicated that Fe2O3/COOH-MWCNT composite is a potential anode material for lithium-ion batteries.
Keywords: anode material; carbon nanotubes; hydrothermal synthesis method; lithium-ion batteries